Efficient micropropagation protocol and genome size estimation of an important cover crop, Mucuna bracteata DC. ex Kurz - Abd Aziz, Nazrin; Tan, Boon Chin; Othman, Rofina Yasmin; Khalid, Norzulaani (Springer, 2018)
Mucuna bracteata DC. ex Kurz is an important cover crop in plantations across the tropics. However, low germination rate and poor viability of Mucuna seeds pose significant challenges of using the seeds as starting material. To address these limitations, we have optimized seed germination conditions (such as scarification period, surface sterilization protocols and imbibition period) and in vitro propagation protocols for M. bracteata. We found that seeds treated with sulphuric acid for 30 min, imbibed for 6 h and incubated in dark conditions on a wet cotton roll (10 mL of sterile distilled water) supplemented with 0.1% activated charcoal produced the highest percentage of seed germination (44%) and seed vigor index. In vitro-derived cotyledonary nodes showed the highest number of shoots per explant (5.60) and rooting response (92.9%) when cultured on Murashige and Skoog medium containing 4.44 µM 6-benzylaminopurine and 10.7 µM 1-naphthaleneacetic acid, respectively. Of the 100 rooted plantlets acclimatized, 89.0% survived after 4 weeks of transplanting. Single sequence repeat and flow cytometry analysis were performed to confirm the genetic fidelity of the plants. Our protocol offers, for the first time, a simple and effective seed germination and scalable propagation procedures for M. bracteata. Furthermore, we have also estimated the genome size (1448 ± 9 Mb) and DNA content (1.48 ± 0.01 pg) for M. bracteata that can be used for future cytogenetic studies on genetic diversity and gene exchange.